COAL BED METHANE POTENCYOF TANJUNG FORMATION IN TANAH BUMBU SOUTH KALIMANTAN - Simatupang, David P; Amarullah, Deddy (Buletin Sumber Daya Geologi, 2010)
Coal deposits distributes widely in Indonesia, mainly in Sumatera and Kalimantan. These deposits become an indication for a huge quantity of coal-bed methane (CBM) potency. As an environmentally friendly source of energy, CBM could be one of Indonesia's future energy sources. Centre for Geological Resources (CGR) started the exploration for this energy since 2005, while the study was conducted in 2008 at Tanjung Formation in Tanah Bumbu Area, South Kalimantan.CSAT-1 well was drilled to provide CBM resources and deep coal mine potency data for Tanjung Formation (Eocene) in Asem-asem Basin. This well went through 10 coal seams with three main seam, which is E seam at 212.34-213.30 m depth, I seam at 261.93-264.20 m, and J seam at 270.20-275.35 m depth. Calorific value from this three main seam categorized as high rank coal, vary from 6197-6745 cal/gram (adb), with total moisture between 4.51-7.11 %, adb.Total coal resources used for CBM resources quantification is 112,733,226 tons (between 300 to 1000 meters depth). Based on desorption test and gas chromatograph measurement from samples at various depth from three main seams, those coal gives methane resources estimation about 430 MSCF, with methane content vary between 1.2 - 6.6 cu-ft/ton of coal.